The Meaning of Wasath: The Return of the Holistic Paradigm of Islam Through the Approach of Tafsir bil Ma'na - Zakiyah, Ermita; Ramadhan, Rivalzaky Echa; Azizah, Imroatul Azizah; Muthohirin, Nafik (Proceedings Conference Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2026)
The concept of wasath in Islam is often associated with the principles of balance, moderation and justice in various aspects of life. However, the partial meaning of wasath often obscures its essence as a holistic paradigm in Islam. This research aims to review the meaning of wasath through the approach of tafsir bil ma'na, which is a tafsir method that emphasises understanding the meaning of the Qur'an contextually and integrally. Using library research and qualitative descriptive analysis of linguistic roots, usage in the Qur'an, as well as the interpretations of classical and contemporary mufasirs, this study finds that wasath is not merely a concept of moderation, but a basic principle in Islamic epistemology that includes theological, social and ethical dimensions. The tafsir bil ma'na approach allows reinterpretation that is more in line with the challenges of the times, restoring wasath as the foundation of Islam's holistic paradigm in facing modern problems. The results of this research are expected to contribute to the study of tafsir and a more comprehensive moderate Islamic discourse.